2018
DOI: 10.1007/s13205-018-1518-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drought stress-responsive root transcriptome of faba bean (Vicia faba L.) using RNA sequencing

Abstract: Drought and salinity are the major factors that limit the faba bean (Vicia faba L.) production worldwide. The aim of this study is to identify the water stress differentially expressed genes (DEGs) through the root transcriptome analyses of the droughttolerant Hassawi 2 genotype at vegetative and flowering stages. A total of 624.8 M high-quality Illumina reads were generated and assembled into 198,155 all-unigenes with a mean length of 738 bp and an N50 length of 1347 bp. Among all-unigenes, 78,262 were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…RNA sequencing (RNA-Seq) makes it possible to capture these genes (Cheng et al, 2017). In recent years, fundamental changes happened for the sequencing technology (Alghamdi et al, 2018). The second generation sequencing (NGS) technology deeply enhanced the efficiency and speed in gene discovery (Mortazavi et al, 2008;Asmann et al, 2009;Hershkovitz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing (RNA-Seq) makes it possible to capture these genes (Cheng et al, 2017). In recent years, fundamental changes happened for the sequencing technology (Alghamdi et al, 2018). The second generation sequencing (NGS) technology deeply enhanced the efficiency and speed in gene discovery (Mortazavi et al, 2008;Asmann et al, 2009;Hershkovitz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) platforms, especially high-throughput RNA sequencing (RNA-seq) technology, one of the most powerful tools currently available for transcriptome profiling, has enhanced the efficiency and speed of gene discovery in faba bean (Table 3). For example, the identification and characterization of differential gene expression from tissues subjected to drought (Alghamdi et al, 2018;Wu et al, 2020), vernalization (Gao et al, 2020), and salinity stress (Yang et al, 2020) have benefited greatly. These findings will help in understanding the stress tolerance mechanisms in the crop and will provide resources for functional genomics.…”
Section: Transcriptomesmentioning
confidence: 99%
“…Identified DEGs were novel and showed substantial change at expression level under drought stress conditions. Consequently, the qRT-PCR results were coinciding with sequencing, which could help for functional genomics and tolerance mechanisms in crop plants (Alghamdi et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, proteomics plays a significant part in the study of differences at cellular, subcellular, and plant levels under abiotic stress conditions (Hossain and Komatsu, 2014). Alghamdi et al (2018) studied seven cowpea genotypes about solubility-based protein analysis; their results revealed that water-soluble proteins were dominant in cowpea seeds when compared to total proteins. Moreover, gel patterns revealed molecular diversity, total protein complement, and the presence of different protein fractions.…”
Section: Introductionmentioning
confidence: 99%